DAMPAK PROGRAM PEMBANGUNAN DESA DI MUARA MAIS KECAMATAN TAMBANGAN KABUPATEN MANDAILING NATAL - Abdullah Rajab Lubis; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Village development is one of the programs that has a big impact on the life of the community in the village, especially in the environmental, economic and social sectors. With the village development program, it is hoped that it can provide support for improving the quality of the environment, improving the economy and social community in the village. However, in reality the development program that has been carried out has not fully been able to have a maximum impact on the lives of the people in Muara Mais Village, both on the environment, economy and society. This study aims to find the impact of village development on community life both on the environment, economy and social of rural communities and to find the inhibiting factors of this development. The theory used in this research is to see the impact of a program or activity (Samudera Wibawa, 1994: 4-5) by using indicators of environmental impact, economic impact and social impact. This type of research is qualitative research with a case study approach. The results of this study found that the impact of the village development program on the environment, economy and social society in Muara Mais Village was good, because there were more positive impacts than negative side effects, although there were still factors inhibiting the development program. that is, limited land for development and human resources that are not responsive to development. Keywords: Program Impact, Village Development, Village Development Program